Analisis Manajemen Laba pada PT Mayora Indah Tbk Menggunakan Model Modified Jones - Nur Fadilah Arsyad (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze earnings management practices at PT Mayora Indah Tbk using the Modified Jones Model to measure discretionary accruals over the 2020-2024 period. A quantitative non-experimental approach was applied, drawing on secondary data from the company's annual financial statements published by the Indonesia Stock Exchange. Calculations encompassed total accruals, computed as the difference between net income and operating cash flow, followed by linear regression to derive coefficients for non-discretionary accruals, thereby yielding discretionary accruals. Findings indicate significant fluctuations in total accruals, with negative values of Rp -1,617.66 billion in 2020 and Rp -2,014.31 billion in 2023, alongside a sharp positive spike of Rp 3,531.03 billion in 2024. Non-discretionary accruals remained consistently negative, ranging from -0.174 to -0.210, indicative of normal operations. In contrast, discretionary accruals were positive throughout all years, peaking at 0.358 in 2024, suggesting potential managerial intervention to inflate performance. These results highlight earnings management risks at PT Mayora Indah Tbk, underscoring the imperative for rigorous oversight to safeguard earnings quality and stakeholder trust.